Important role of learning Institution in Bangladesh and the activities of training and development Institution Listeners and Speakers Forum (LSF) - Tarin, Sonia Alam (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.